Reframing SpO2 tolerance as a physiological switch: implications for hypoxic adaptation and exercise regulation - Yuri, Enomoto; Chung, Hui-Yu; Chen, Fu-Shih (Frontiers in Physiology, 2025)
Blood oxygen saturation (SpO2) is a widely used oxygenation index in clinical and physiological settings. However, recent phenomena, such as asymptomatic hypoxia in COVID-19 and the superior performance of athletes in high-altitude conditions under hypoxia, have highlighted the significant variability in individual tolerance to blood oxygen saturation. Age, health status, disease, and hypoxic adaptation influence it. This brief review introduces the concept of the SpO2 switch as a dynamic. We also proposed a physiological compensatory response of SpO2 switch to SpO2 criticality that triggers compensatory responses, including ventilatory, autonomic, cardiovascular, and metabolic adaptations. Furthermore, individuals can exhibit markedly different responses to hypoxia at the same SpO2 value. It reflects a “threshold switch mechanism” driven by an individual’s internal physiological settings. This suggests that the SpO2 value demonstrates the onset of hypoxia symptoms and reacts to the body’s difference in compensatory capacity. This reconceptualisation shifts the focus from static thresholds to dynamic response analysis, offering new perspectives for precision health, mountain medicine, and personalised risk assessment of hypoxia.